The Effect of Leadership Style and Work Motivation on Employee Performance PT Permodalan Nasional Madani Lampung Branch - Deden Yoga Nugraha; Agus Salim (Dinasti International Journal of Education Management And Social Science, 2023)
The purpose of this study was to analyse the effect of work motivation and leadership style on employee performance (PT. Permodalan Nasional Madani Lampung Branch) partially. The sampling technique used was purposive sampling technique in which a total of 131 employees were sampled. Data collection techniques using questionnaires and interviews. This research uses qualitative descriptive techniques with data analysis techniques using multiple linear analysis and classical assumption tests. Data processing using SPSS software version 24. The results obtained found a significant effect on work motivation variables on employee performance. Different results showed no significant effect of leadership style variables on employee performance.